The Effects of Thrombin on Adenyl Cyclase Activity and a Membrane Protein from Human Platelets - Brodie, G. N. (1972)
Washed human platelets were incubated with 0.1-1.0 U/ml human thrombin and the effects on adenyl cyclase activity and on a platelet membrane protein (designated thrombin-sensitive protein) were studied. Adenyl cyclase activity was decreased 70-90% when intact platelets were incubated with thrombin. The T½ for loss of adenyl cyclase activity was less than 15 sec at 1 U/ml thrombin. There was no decrease of adenyl cyclase activity when sonicated platelets or isolated membranes were incubated with these concentrations of thrombin. Loss of adenyl cyclase activity was relatively specific since the activities of other platelet membrane enzymes were unaffected by thrombin. Prior incubation of platelets with dibutyryl cyclic adenosine monophosphate (AMP), prostaglandin E(1), or theophylline protected adenyl cyclase from inhibition by thrombin. Incubation of intact but not disrupted platelets with thrombin resulted in the release of thrombin-sensitive protein from the platelet membrane. The rapid release of this protein (T½ < 15 sec) at low concentrations of thrombin suggested that removal of thrombin-sensitive protein from the platelet membrane is an integral part of the platelet release reaction. This hypothesis is supported by the parallel effects of thrombin on adenyl cyclase activity and thrombin-sensitive protein release in the presence of dibutyryl cyclic AMP, prostaglandin E(1), and theophylline at varying concentrations of thrombin.